Bring on the bling! bracelets, anklets, and rings for all occasions - Prestine, Debbie Prestine; Kachidurian, Kelly; Kachidurian, Megan (North Mankato, Minnesota Capstone Press, a Capstone imprint, 2017)
"Step-by-step instructions teach readers how to create bracelets, anklets, rings, and other jewelry accessories
A gift from book Africa
Jewelry
1 2 13 15
NEW_ZTN_GN
Keywords: Bracelets -- Juvenile literature; Jewelry making -- Juvenile literature